两条解方程 3.6x-x=3.25 2X(x-3)=5.8
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:09:13
两条解方程3.6x-x=3.252X(x-3)=5.8两条解方程3.6x-x=3.252X(x-3)=5.8两条解方程3.6x-x=3.252X(x-3)=5.83.6x-x=3.252X(x-3)=
两条解方程 3.6x-x=3.25 2X(x-3)=5.8
两条解方程 3.6x-x=3.25 2X(x-3)=5.8
两条解方程 3.6x-x=3.25 2X(x-3)=5.8
3.6x-x=3.25 2X(x-3)=5.8
2.6x=3.25 2x-6=5.8
x=3.25/2.6=1.25 2x=5.8+6
2x=11.8
x=5.9
X=3.25/2.6
x=3
3.6x-x=3.25
(3.6-1)x=3.25
2.6x=3.25
x=3.25÷2.6
x=1.25
2x(x-3)=5.8
2x²-6x=5.8
10x²-30x-29=0
由求根公式得:
x =(15-√515)/10
或:
x =(15+√515)/10
两条解方程 3.6x-x=3.25 2X(x-3)=5.8
解方程3.6X-X=3.25
3.6x-x=3.25方程怎样 .
3.6x-x=3.25方程
X+2X+6X=3.6怎么解方程
解方程:(x+2)(x+2)-x*x=36
2X(x+1.5x)=5x 解方程
解方程;x/x-4=5x/x-2
解方程(63-x)-x/2=x-(63-x)
解方程 0.8X*(X+2)=X*X
解方程 0.8X*(X+2)=X*X
解方程:x(x-4)=(x-2)(x-6)
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
5x+7=42 x÷4.2=2 3.6x-x=3.25 2(x-5x+7=42 x÷4.2=2 3.6x-x=3.25 2(x-3)=5.8.解方程
3.6X-X=3.25要方程,2(x-3)=10.
解方程(x/x(x+2))+(x/(x+2)(x+4))+.+x/(x+8)(x+10)=1
x-0.35x=3.25解方程.
8.6X-x=3.25用方程